2021
DOI: 10.1002/pmic.202000160
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II immunopeptidomics reveals that co‐inherited HLA‐allotypes within an extended haplotype can improve proteome coverage for immunosurveillance

Abstract: Human leucocyte antigen (HLA) class II molecules in humans are encoded by three different loci, HLA‐DR, ‐DQ, and ‐DP. These molecules share approximately 70% sequence similarity and all present peptide ligands to circulating T cells. While the peptide repertoires of numerous HLA‐DR, ‐DQ, and ‐DP allotypes have been examined, there have been few reports on the combined repertoire of these co‐inherited molecules expressed in a single cell as an extended HLA haplotype. Here we describe the endogenous peptide repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…Consistently, glycosylated and non-glycosylated peptides from Ramarathinam et al 2021 showed similar binding properties, indicating that the detected glycosylation fit within the known HLA-binding cores (two-tailed Fisher's exact test, P-value: 0.48). Interestingly, .…”
Section: Deconvolution Of Peptides Using a Fully Unsupervised Approachmentioning
confidence: 63%
See 3 more Smart Citations
“…Consistently, glycosylated and non-glycosylated peptides from Ramarathinam et al 2021 showed similar binding properties, indicating that the detected glycosylation fit within the known HLA-binding cores (two-tailed Fisher's exact test, P-value: 0.48). Interestingly, .…”
Section: Deconvolution Of Peptides Using a Fully Unsupervised Approachmentioning
confidence: 63%
“…We carefully selected a case study on a human B lymphoblastoid cell line (C1R) from Ramarathinam et al . 2021 36 . The purification protocol of the HLA-bound peptides in this study was performed sequentially with pan anti-class I, followed by class II anti-DP ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To expand the results obtained in the current study to other HLA-DR and -DP allotypes as well as the HLA-DQ locus, the analysis of the 5856 parental proteins containing HLA class II ligands previously reported was carried out. Up to 86% of our parental protein data set was present in the pool of these studies.…”
Section: Resultsmentioning
confidence: 99%